Inovasi Teknologi Budidaya Padi Unggul di Lahan Rawa Pasang Surut Tipe Luapan C - Yanti Rina Darsani; Muhammad Alwi (Jurnal Sosial Ekonomi Pertanian, 2022)
In the future, the tidal swampland will play an important role in increasing rice production to support food self-sufficiency. Acceleration of food self-sufficiency can be done through the demonstration of rice cultivation technology plots. To obtain an adaptive integrated management technology package to support rice development in tidal swamplands, dissemination activities were carried out on farmers' land in Matang Danau Village, Paloh District, Sambas Regency, West Kalimantan Province. The activities were carried out in the 2018 dry season (MK), 2018/2019 rainy season (MH), and 2019 dry season (MK). Each activity covered an area of 50 ha consisting of 5 ha of introduced technology packages (P1) and 45 ha of farmer technology packages (P2). The technology applied consists of the use of high yield rice variety, land preparation, water management, 2: 1 jarwo planting system, and nutrient management. Data collection was carried out through daily activity records and surveys. The results of the dissemination activity showed that superior rice yields in the 2018 dry season ranged from 2.44 - 5.39 tons/ha Milled Dry Grain (GKG), 2018/2019 rainy season ranged from 7.3 - 8.4 tons/ha GKG and 2018 dry season ranged from 2.4 - 4.4 tons/ha GKG. Economically, from the improvement of high yield rice variety technology with 8 varieties in the 2018 dry season, 5 varieties in 2018/2019 rainy season, and 6 varieties in 2019 dry have good prospects to be developed on a broad scale. The Farmers' perceptions on introduced high yield rice variety cultivation on agree rating scale.